2017
DOI: 10.1016/j.stemcr.2017.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Transplantation of Embryonic Stem Cell-Derived Cone Photoreceptors into a Mouse Model of End-Stage Retinal Degeneration

Abstract: SummaryThe loss of cone photoreceptors that mediate daylight vision represents a leading cause of blindness, for which cell replacement by transplantation offers a promising treatment strategy. Here, we characterize cone differentiation in retinas derived from mouse embryonic stem cells (mESCs). Similar to in vivo development, a temporal pattern of progenitor marker expression is followed by the differentiation of early thyroid hormone receptor β2-positive precursors and, subsequently, photoreceptors exhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 46 publications
2
72
1
Order By: Relevance
“…In another elegant study, improvement of vision impairment was successfully demonstrated following transplantation of functional rod photoreceptors in adult Gnat1 -/mice, which lack rod function as a model of congenital stationary night blindness [78]. Therefore, generation of transplantationcompetent photoreceptor precursors from hPSCs has been investigated to treat blindness [79][80][81][82].…”
Section: (A) Disease Modellingmentioning
confidence: 99%
“…In another elegant study, improvement of vision impairment was successfully demonstrated following transplantation of functional rod photoreceptors in adult Gnat1 -/mice, which lack rod function as a model of congenital stationary night blindness [78]. Therefore, generation of transplantationcompetent photoreceptor precursors from hPSCs has been investigated to treat blindness [79][80][81][82].…”
Section: (A) Disease Modellingmentioning
confidence: 99%
“…Similar findings have been achieved using photoreceptor cells obtained from 3D cultures of pluripotential stem cells (PSCs) from both murine and human sources. [7][8][9] More recently, however, we, and others, [10][11][12] have shown that when transplanted into models of slow or partial degeneration, where significant numbers of recipient photoreceptors still remain, the donor photoreceptors do not integrate within the host retina, but instead undergo an unusual process of material transfer. This involves the robust exchange of material (RNA and/or protein) between donor and host photoreceptors, rendering the host acceptor photoreceptor cells functional.…”
Section: Introductionmentioning
confidence: 98%
“…Photoreceptor transplantation is being developed as a therapeutic modality to restore vision in people affected by retinal degenerative diseases, including retinitis pigmentosa (RP) and age-related macular degeneration (AMD) 16 . Short term improvements in outer retinal anatomy after photoreceptor cell transplantation have been observed, mainly by histological staining in preclinical models of retinal degeneration 4,7 . However, histology is a relatively inefficient method to track graft and recipient anatomy longitudinally over the long term.…”
Section: Introductionmentioning
confidence: 99%